Participation of MDM2 in Pro-Apoptotic and Androgen Receptor-Degrading Potency of Selected Steroid and Terpenoid Derivatives - Misharin, Alexander Y.; Veselovsky, Alexander V.; Zolottsev, Vladimir A. (Current Medicinal Chemistry, 2025)
This review aims to highlight anti-proliferative, pro-apoptotic, and androgen receptor-degrading activity of selected steroid and terpenoid derivatives in cancer cells, primarily in prostate cancer cells. Steroid and terpenoid derivatives (steroid hybrids, comprising androstane or pregnane skeleton associated with nitrogen containing heterocycle, some natural sterols, bile acids, and related semi-synthetic derivatives; oleanane and ursane type pentacyclic triterpenoids; lanostane and dammarane type tetracyclic triterpenoids), were reported earlier to cause the death of cancer cells <span class=
Keywords: MDM2